Factors Influencing Mortality Rates of Murrah Buffaloes in an Organised Farm of Andhra Pradesh - Rao, K. Ananada; Kumari, G. Deepika (International Journal of Livestock Research, 2021)
Andhra Pradesh’s coastal region has the largest population of cattle and buffaloes both in organised sectors as well as backyard farming by farmers. Buffalo research station in Venkataramannagudem, West Godavari is located in Andhra Pradesh, maintains nearly 160 Murrah buffaloes and is managed by Sri Venkateswara Veterinary University. The data on mortality of buffaloes in the farm was collected for the past six years and was categorised based on sex and age. The data was analysed using standard statistical methods. The present studies reported an overall mortality rate of 2.92%. It was noted that mortality was higher in adults than in calves and there is no much sex variation in the death of the calves. The mortality rate was very less in the farm over the past six years reciprocating the strict managemental practices that were carried in the organised farm.